Youth Welfare and the Practice of German Reformatories in the Weimar Republic: Between Social Reintegration and Exclusion of the "Behaviorally Maladjusted" - Harder, Jürgen (Social justice, 2011)
The article discusses German reformatories, established and run by religious organizations, for young men during the Weimar Republic in Germany from 1919-1933. It particularly focuses on an essay written by a resident of a reform school criticizing the practice of correctional education, commenting on the historical perception of a crisis of educational, economic, and conceptual problems among the German youth. Other topics explored include the influence of social Darwinism on education, the reintegration of reformed inmates into wider society, and the development of youth welfare in early 20th century Germany.